(untitled) - Rajesh Kumar Yadav; Teena Bagga; Seema Johar (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
Ease of doing business index provides aggregate figures of country?s operational business environment. World bank publishes ease of doing business reports, ranking respective countries at par with accessible business ecosystem. E-governance was one of the most important factors considered for ease of doing business indexing. Moreover, E-governance was the platform government utilizes for sharing information, operationalizing transactions and integrating service on offer. E-governance therefore, waspredominantly used by governments in providing information, communication and technology (ICT) related services to citizens of the country. In addition to ease of doing business, e-governance was also impacted by a host of other factors. There were many international research studies identifying factors related to ease of doing business. Therefore, the purpose of this research study is to find out various factors which impacts ease of doing business in India concluding that e-governance and internet readiness matters for better ease of doing business.